DEVELOPMENT STRATEGIES FOR SERMIER CRACKERS TO INCREASE INCOME FOR THE COMMUNITY OF WANTILGUNG VILLAGE, NGAWEN DISTRICT, BLORA REGENCY - Silfia, Serli; Ajeng Andriyani Hapsari (Study of Applied Entrepreneurship, 2024)
Sermier crackers, a type of cracker made from cassava, have been a longstanding traditional snack. Their unique, distinct, and delicious taste, combined with their affordability, makes them comparable to other flavored crackers. However, the popularity of these crackers has been declining due to advancements in food management and a growing preference among consumers to try new foods. The lack of innovation from food producers may also contribute to a reduced interest in traditional Indonesian foods. This study aims to identify methods and strategies to develop a cassava-based cracker business in Wantilgung Village, Ngawen District, Blora Regency. Data were collected through a field survey involving 125 respondents. The analysis of sermier crackers revealed the following financial metrics: an initial investment of Rp. 1,093,000, total asset costs of Rp. 36,430, total variable costs of Rp. 1,620,000, total operational costs of Rp. 1,664,430, monthly revenue of Rp. 7,200,000, a profit of Rp. 5,543,570, and a payback period of two months. A SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) was employed to identify aggressive alternative strategies for the sale of sermier crackers. The data utilized in this study included primary, quantitative, and secondary data sources.